Quintuple‐Shelled SnO2 Hollow Microspheres with Superior Light Scattering for High‐Performance Dye‐Sensitized Solar Cells. (22nd October 2013) - Dong, Zhenghong; Ren, Hao; Hessel, Colin M.; Wang, Jiangyan; Yu, Ranbo; Jin, Quan; Yang, Mei; Hu, Zhudong; Chen, Yunfa; Tang, Zhiyong; Zhao, Huijun; Wang, Dan
<x xml:space="preserve">Abstract</x> Quintuple‐shelled SnO2 hollow microspheres are prepared by a hard‐template method. DSSCs constructed with SnO2 multi‐shell photoanodes show a record photoconversion efficiency of 7.18% due to enhanced light scattering. SnO2 hollow microspheres that are utilized as a scattering layer on top of P25 films increase the DSSC photoconversion efficiency from 7.29% to 9.53%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>